Slice Interpolation for MRI Using Disassemble-Reassemble Method - Qinghua Lin; Min Du (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Due to physical limitations inherent in Magnetic resonance image (MRI) scanners, the inter-slice resolution of MRI is coarse. Thus, interpolation is often used to compensate it. MRI corresponds to a thin slice through the human body, and contains all the information in the slice. Based on this characteristic, a novel slice interpolation algorithm using disassemble-reassemble (D-R) method is proposed for doing MRI slice interpolation. The algorithm first disassembles all the information contained in MRI, and then reassembles them under a heuristic approach of neighborhood consistency to get higher inter-slice resolution. Series virtual images that imitate the characteristic of MRI were used to explain the principle of proposed algorithm, and the process of proposed algorithm was derived from detail analysis. Finally, we performed a large number of interpolation experiment and compared the proposed algorithm to several other interpolation techniques. Results show that the proposed algorithm outperforms the other interpolation algorithms, which means the D-R method is more suitable for MRI interpolation.